The total torsion element graph of semimodules over commutative semirings - Ebrahimi Atani, S.; Esmaeili Khalil Saraei, F. (Algebra and Discrete Mathematics, 2013)
We introduce and investigate the total torsion element graph of semimodules over a commutative semiring with non-zero identity. The main purpose of this paper is to extend the definition and results given in [2] to more general semimodule case.